Haptyczne dokumenty o dźwięku i muzyce - Topolski, Jan (Humaniora. Czasopismo Internetowe, 2025)
The article is an analysis of four documentary films about experimental music at the turn of the 20th and 21st centuries: “Step Across the Border” (1990), “Touch the Sound” (2004), “15 Corners of the World” (2014), and “Preemptive Listening” (2024). The main theoretical context is the sensory theory of cinema (Laura U. Marks and Marta Stańczyk), audio-vision (Michel Chion), and affective theories (Luis-Manuel Garcia, Brian Massumi). The creators of these films translate sound into image and vice versa in various ways, with the key areas of this exchange being synesthesia, multimodality, and texture. Evelyn Glennie, who appears in two of the four films, emerges as the leading character and symbol of this new type of perception.